Acute pulmonary edema secondary to severe preeclampsia in a 47-year old elderly gravida conceived via in vitro fertilization: a case report - Venkatesh, Madhumitha; Mathimaaran, Sneha; Narayanan, Palaniappan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Advanced maternal age and assisted reproductive technologies, such as in vitro fertilization (IVF) with oocyte donation, are recognized as risk factors for many disorders in pregnancy, including preeclampsia. Severe preeclampsia can, in rare instances, be complicated by acute pulmonary edema, posing significant risks to both the mother and the fetus. We report a rare case of a 47-year-old elderly primigravida with a BMI of 30 kg/m² (obese) who conceived via IVF and developed severe preeclampsia at 30+5 weeks of gestation with a hypertensive crisis that progressed to cause a life-threatening acute pulmonary edema. Immediate management included intravenous antihypertensives, diuretics, magnesium sulphate, and ventilatory support. Due to the deteriorating maternal and fetal status, an emergency lower segment caesarean section was performed in the intensive care unit. A 1.2 kg baby girl was delivered and admitted to the neonatal intensive care unit. The mother showed gradual postoperative improvement with stabilization of blood pressure and resolution of pulmonary symptoms. Her recovery period was aided by a multidisciplinary team involving obstetricians, anaesthesiologists, neonatologists, intervention specialists, and clinical psychologists. The case emphasizes the need for heightened vigilance and aggressive management in IVF pregnancies especially among women of advanced maternal age who are at increased risk of hypertensive disorders, fluid shifts, and cardiovascular stress. Risk assessment in elderly women undergoing IVF is crucial, along with vigilant monitoring and prompt multidisciplinary intervention to improve outcomes in high-risk pregnancies.